Metal-organic frameworks for precise inclusion of single-stranded DNA and transfection in immune cells - Shuang Peng (Nature Portfolio, 2018)
Non-viral vectors are important for transfection but can be limited in the uptake, protection and release of ssDNA. Here, the authors report on the design of metal-organic-framework vectors with precisely controlled pore geometry and demonstrate the vector in the transfection of immune cells.